Method for manufacturing sheet metal components from flat steel products provided with a corrosion-protective coating - Patents.com

JP2022535056A5Active Publication Date: 2025-01-07THYSSENKRUPP STEEL EUROPE AG PATENTE PATENT DEPARTMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021571660
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2020-05-28
Publication Date
2025-01-07
Estimated Expiration
2040-05-28

AI Technical Summary

Technical Problem

Existing methods for manufacturing sheet metal components from flat steel products with corrosion protection coatings fail to meet high requirements for weldability and adhesion of organic coatings, particularly during resistance welding and application of organic layers, due to issues with hydrogen embrittlement and porosity in the corrosion protection coating.

Method used

A method involving annealing flat steel products in a continuous furnace with specific dew point and temperature zones, followed by application of an aluminum-based corrosion protection coating, ensures a homogeneous and reduced-porosity coating with an iron-aluminum layer, optimizing conductivity and adhesion for subsequent hot forming and organic coating application.

Benefits of technology

The method reduces porosity and improves weldability and adhesion of organic coatings, minimizing hydrogen embrittlement and enhancing the overall performance of sheet metal components by ensuring a uniform and defect-free corrosion protection coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a sheet metal component, in which a) a flat product made of steel is provided, the steel consisting of (in % by weight) 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, ≦0.06% P, ≦0.01% S, ≦1.0% Al, ≦0.15% Ti, ≦0.6% Nb, ≦0.01% B, ≦1.0% Cr, ≦1.0% Mo, where the sum of the Cr and Mo contents is ≦1.0%, ≦0.2% Ca, ≦0.1% V, the balance being iron and impurities; and b) the flat product is annealed in a continuous furnace having four zones A, B, C, D at a dew point temperature TP and an annealing temperature GT under an annealing atmosphere consisting of 0.1-15% hydrogen and nitrogen, wherein the following applies: Zone A TP: -10 to -25°C, GT: 800 to 950°C, Zone B TP: -27 to -41°C, GT: 800 to 930°C, Zone C TP: -30 to -80°C, GT: 800 to 950°C, Zone D TP: -30 to -20°C, GT: 750 to 950°C; c) applying a corrosion-protective coating consisting of (by weight) <15% Si, ≦5% Fe, a total of 0.1 to 5% of at least one alkaline earth or transition metal, the balance being Al and unavoidable impurities, to a flat steel product; optionally d) decoratively rolling the flat steel product; e) separating boards from the flat steel product; f) heating the flat steel product to > the Ac3 temperature of the steel of the flat steel product and ≦1000°C for a holding time sufficient to introduce a thermal energy amount >100,000 to 800,000 kJ; g) hot-forming the flat steel product into a sheet metal component; h) cooling at least one portion of the component at a cooling rate sufficient to produce a hardened structure. The present invention also provides a component in which optimized adhesion of the corrosion-protective coating to the steel substrate is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for manufacturing sheet metal components from flat steel products that have been coated with a corrosion-resistant coating. [Background technology]

[0002] Here, flat steel products are understood to be rolled products in which the length and width are significantly greater than the thickness. These flat steel products include, in particular, steel strips and steel sheets.

[0003] Unless otherwise explicitly stated, information regarding the content of alloy components in this text is always provided in weight percent.

[0004] On the other hand, the proportions of specific components of the atmosphere, particularly the annealing atmosphere, are expressed in volume percent unless otherwise noted.

[0005] The first type of method described is known from Patent Document 1. A flat steel product is used as the starting product for this method, and its steel substrate consists of so-called "MnB steel." This type of steel is standardized in EN10083-3 and has good hardenability. They enable reliable process control during hot pressing, thereby economically allowing martensitic hardening to occur within the tool during hot forming without additional cooling. A typical example of such steel is the steel known as 22MnB5, which can be found as material number 1.5528 in Key to Steel 2004. Typically, fully solidified 22MnB5 steel available on the market contains, in addition to iron and unavoidable impurities, 0.10–0.250% C, 1.0–1.4% Mn, 0.35–0.4% Si, up to 0.03% P, up to 0.01% S, up to 0.040% Al, up to 0.15% Ti, up to 0.1% Nb, a total of up to 0.5% Cr+Mo, and up to 0.005% B (in weight%). To protect flat steel products made from such composite steels from corrosion and at the same time minimize the risk of hydrogen absorption during heating required for hot forming, the flat steel products are coated with an aluminum-based corrosion protection coating by known methods, which contains at least one alkaline earth or transition metal in an effective content as an additional alloying component of 0.005–0.7% by weight. In addition, the coating may also contain 3–15% by weight of Si and up to 5% by weight of Fe. As at least one alkaline earth or transition metal in the protective coating, Mg is preferably used here in a content of 0.1–0.5% by weight, with calcium, strontium, sodium, or barium being alternative or additional. The Al-based protective coating can be deposited on the steel substrate by hot-dip coating, also known by the technical term "hot-dip aluminizing," or by gas separation processes such as known PVD (physical vapor deposition) or CVD (chemical vapor deposition).

[0006] No special requirements for the method of applying a corrosion-protective coating to a steel substrate made of MnB steel are mentioned in the prior art described above. When a board coated using the above method is heated to a temperature of 900°C for a period of 360 to 800 seconds in a conventional manner under normal atmospheric conditions, only minimal hydrogen absorption occurs in the steel substrate due to the presence of alkaline earth or transition metals in the coating, thus minimizing the risk of so-called "hydrogen embrittlement."

[0007] However, in actual use, despite this success, it has been found that while components formed from flat steel products manufactured using the above method have optimized strength, they cannot always meet the increasingly stringent requirements for the behavior of these sheet metal components in the case of resistance welding of such flat steel products, or in the bonding of organic layers, such as by coating.

[0008] Patent Document 2 also deals with a method for manufacturing aluminum-based steel components with a metal corrosion-resistant coating. For this purpose, a flat steel product is provided, which consists of 0.15-0.50% C, 0.50-3.0% Mn, 0.10-0.50% Si, 0.01-1.00% Cr, up to 0.20% Ti, up to 0.10% Al, up to 0.10% P, up to 0.1% Nb, up to 0.01% N, up to 0.05% S, and up to 0.1% B, the remainder Fe and unavoidable impurities, and is coated with an Al coating, which consists of 3-15% Si, 1-3.5% Fe, up to 0.5% alkali and / or alkaline earth metals, the remainder Al and unavoidable impurities, in weight percent. The provided sheet metal is annealed in an oven at a certain temperature for a certain period of time, with the temperature and period being correlated by parameters calculated using a complex formula. Depending on the furnace residence time and temperature, a so-called interdiffusion zone is formed in the transition area between the substrate and the coating, where no martensitic structure is formed during press hardening, and this is also not assigned to the Al coating. This interdiffusion zone starts from the center of the flat steel product and extends from a thickness where no further martensitic structure exists in the component to a thickness where the iron content of the Al coating is continuously ≤85 wt% and the Al content is continuously ≥10 wt%. Neither detailed information on how the interdiffusion zone could be designed nor an explanation of how the formation and composition of the interdiffusion zone could be controlled by targeting methods relating to specific surface properties of the coating is provided in this prior art. Instead, the focus here is on the deformation behavior of the Al coating, particularly considerations for improving the achievable bending angle. [Prior art documents] [Patent Documents]

[0009] [Patent Document 1] European Patent Application Publication No. 2 993 248(A1) [Patent Document 2] German Patent Application Publication No. 10 2017 210 201(A1)

Summary of the Invention

Means for Solving the Problems

[0010] In view of this background, an object has emerged of showing a method that enables the formation of sheet metal components from flat steel products of the type described above, which have optimal conditions for coating, especially for application, by means of an organic coating while meeting the highest requirements for weldability.

[0011] To achieve this object, the present invention proposes that at least the method steps shown in claim 1 are completed during the production of the sheet metal component.

[0012] Of course, when implementing the method according to the present invention, a person skilled in the art not only performs the method steps mentioned in the claims and described here, but also performs all other steps and operations that are usually carried out in the actual implementation of such methods in the prior art if necessary.

[0013] Advantageous embodiments of the present invention are defined in the dependent claims and are explained in detail below in the same way as the general concept of the present invention.

[0014] In the method according to the present invention for producing sheet metal components from flat steel products provided with a corrosion protection coating, therefore at least the following working steps are carried out. a) A step of providing a flat steel product manufactured from steel, wherein the steel consists of (in weight %) 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01% S, up to 1.0% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, where the total content of Cr and Mo is 1.0% or less, up to 0.2% Ca, up to 0.1% V, and the remainder being iron and unavoidable impurities. b) A step of annealing flat steel products in a continuous furnace having four zones A, B, C, and D, wherein the flat steel products pass through these zones sequentially, and in each zone the flat steel products are annealed in an annealing atmosphere consisting of 0.1 to 15 volume percent hydrogen and the remainder nitrogen and technically unavoidable impurities, where the annealing temperature GT A , GT B , GT C , GT D Dew point temperature TP A , TP B , TP C , TP D The following specifications apply to the annealing step:

[0015] [Table 0]

[0016] c) A step of applying a corrosion-protective coating to the flat steel product obtained in step b), wherein the corrosion-protective coating consists of (by weight) up to 15% Si, up to 5% Fe, a total of 0.1 to 5% at least one alkaline earth or transition metal, and the remainder being Al, d) Optionally, a step of decorative rolling of a flat steel product that has been coated with a corrosion-resistant coating, e) Optionally, a step of separating the board from the flat steel product, f) A step of heating the flat steel product or board to a hot forming temperature higher than the Ac3 temperature of the steel of the flat steel product and not exceeding 1000°C for a holding time sufficient to introduce a thermal energy amount J higher than 100,000 kJ and not exceeding 800,000 kJ into the flat steel product or board. g) A step of hot forming a sheet metal component by hot forming a flat steel product or a board heated to a hot forming temperature, h) A step of cooling at least one portion of the component at a cooling rate sufficient to generate a hardened structure in that portion of the sheet metal component.

[0017] The present invention is based on the knowledge that, with respect to the behavior of sheet metal components coated with an aluminum-based ("Al-based") corrosion protection coating, and in the case of resistance welding to such sheet metal components, and in the adhesion, particularly application, of organic coatings, the issue is not only the composition of the boundary layer between the corrosion protection coating and the surrounding atmosphere, but also parameters such as the overall roughness and conductivity of the coating play a decisive role. In this case, the method of performing annealing (working step b)) according to the present invention before applying the corrosion protection coating (working step c)) creates conditions for the component processed according to the present invention to have an optimally homogeneous corrosion protection coating.

[0018] Therefore, components manufactured according to the present invention typically have a corrosion-protective coating, which is formed by multiple layers of different compositions. By guiding the dew point and annealing temperature according to the present invention during annealing in a continuous annealing furnace, and preparing for the subsequent application of the corrosion-protective coating, a significant reduction in pores contained in the coating is achieved.

[0019] The annealing parameters selected according to the present invention during the annealing before coating (work step b)) ensure that at least 70% of the surface of the completed annealed flat steel product is composed of pure iron ("Fe"). This results in good adhesion of the subsequently applied Al-based coating, due to the formation of an iron-aluminum layer ("Fe-Al layer") at the transition from the steel substrate to the corrosion-protective coating. On the other hand, the iron reaches the layer with sufficient and homogeneous uniformity, thereby improving the conductivity of the layer and optimizing its behavior during resistance welding.

[0020] If the flat steel product provided in step b) is already a blank suitable for directly forming components, step e) may be omitted. On the other hand, if the flat steel product provided is a steel strip or a larger steel sheet, boards of a suitable size are separated therefrom in step e).

[0021] The flat steel products annealed and coated (working step b), c)) or separated (working step e)) boards according to the method of the present invention are heated to a hot forming temperature (working step f)) for hot forming (working step g)). Iron already present in the homogeneous boundary layer of the corrosion-protective coating can diffuse uniformly into the coating without any significant defects. At the same time, the alkaline earth or transition metals provided according to the present invention in the corrosion-protective coating diffuse to the surface due to their oxygen affinity, forming an oxide layer therein. Because of their similar atomic size, iron atoms can exchange places with alkaline earth or transition metal atoms in a 1:1 ratio and thus become incorporated into the metal grid, so that the diffusion of alkaline earth or transition metal atoms can result in at most a negligible number of defects. As a result of the reduction of defects achieved by the present invention, these defects cannot aggregate to form pores in the corrosion-protective coating of the component according to the present invention, and therefore the component according to the present invention is characterized by a significantly reduced number of pores compared to conventionally manufactured components, such as those manufactured using the sample of European Patent No. 2086755(B1).

[0022] The effects used in the present invention are particularly reliable when the additionally present alkaline earth or transition metal is magnesium ("Mg"), that is, when Mg is present alone or in combination with other elements belonging to the alkaline earth or transition metal group in the corrosion-protective coating of flat steel products treated according to the present invention.

[0023] The method according to the present invention is suitable for manufacturing components from flat steel products having a wide range of thicknesses. Therefore, flat steel products having a thickness of 0.6 to 7 mm can be processed by the method according to the present invention.

[0024] The production of the flat steel product provided in step a) can be carried out in any manner known from the prior art. The method according to the present invention is particularly suitable for processing flat steel products having a thickness of 0.8 to 4 mm, and especially 0.8 to 3 mm. Flat steel products with a greater thickness than 3 mm are usually processed in a hot-rolled state, while thinner sheets are usually provided in a cold-rolled state.

[0025] In step a), flat steel products having different thicknesses obtained by flexible or partial rolling over length and / or width may be provided for the method according to the present invention. Similarly, in step a) for the method according to the present invention, flat steel products consisting of different sheet metal blanks welded together, or flat steel products consisting of similarly constructed flat steel products and steel strips welded together to form a flat steel product to be processed, may be provided for the process according to the present invention.

[0026] In each case, the flat steel products provided according to the present invention consist of steel having a typical composition for MnB steel. Such steel typically has a yield strength of 250–580 MPa and a tensile strength of 400–720 MPa in the supplied state.

[0027] Therefore, the flat steel product provided according to the present invention consists of the following: - 0.05 to 0.5% by weight of carbon ("C"), where the C content is preferably 0.07 to 0.4% by weight. - 0.5 to 3% by weight of manganese ("Mn"), where the Mn content is preferably 0.8 to 2.5% by weight, and particularly 1.0 to 2.0% by weight. - 0.06 to 1.7% by weight of silicon ("Si"), where the Si content is preferably 0.06 to 1.1% by weight, and particularly 0.06 to 0.9% by weight. - A maximum of 0.06% by weight of phosphorus ("P"), and this P content is 0.03% by weight or less. - Maximum 0.01% by weight of sulfur ("S") - A maximum of 1.0 wt% aluminum ("Al"), wherein the Al content is preferably 0.5 wt% or less, and particularly 0.1 wt% or less. - Up to 0.15% by weight of titanium ("Ti") - A maximum of 0.6% by weight of niobium ("Nb"), wherein the Nb content is preferably a maximum of 0.1% by weight. - A maximum of 0.01% by weight of boron ("B"), wherein the B content is preferably a maximum of 0.005% by weight. - A maximum of 1.0 wt% chromium ("Cr"), wherein the Cr content is preferably a maximum of 0.5 wt%, and more preferably a maximum of 0.2 wt%, - A maximum of 1.0% by weight of molybdenum ("Mo"), wherein the Mo content is preferably a maximum of 0.5% by weight, and more preferably a maximum of 0.2% by weight. - Here, the following applies to the Cr content (%Cr) and Mo content (%Mo): %Cr+%Mo≦1% by weight, - Optionally, up to 0.2% by weight, especially up to 0.1% by weight of calcium ("Ca"), - Optionally, up to 0.1 wt% vanadium ("Va"), Also, the remaining iron and unavoidable impurities.

[0028] Flat steel products are of particular interest in practice because, due to their characteristic profiles, they have the potential to develop high strength, especially in the finished components after hot forming and cooling. Flat steel products are themselves of particular interest in practice because they consist of 0.07-0.4 wt% C, 1.0-2 wt% Mn, 0.06-0.4 wt% Si, up to 0.03 wt% P, up to 0.01 wt% S, up to 0.1 wt% Al, up to 0.15 wt% Ti, up to 0.6 wt% Nb, up to 0.005 wt% B, up to 0.5 wt% Cr, and up to 0.5 wt% Mo, in known ways, because the combined content of Cr and Mo is 0.5 wt% or less, with the remainder consisting of iron and unavoidable impurities.

[0029] This already contains steel that has been used sequentially, which consists of 0.07 - 0.4 wt% C, 1.0 - 1.5 wt% Mn, 0.3 - 0.4 wt% Si, maximum 0.03 wt% P, maximum 0.01 wt% S, maximum 0.05 wt% Al, maximum 0.15 wt% Ti, maximum 0.6 wt% Nb, maximum 0.005 wt% B, maximum 0.5 wt% Cr, maximum 0.5 wt% Mo, where the total content of Cr and Mo is 0.5 wt% or less, and consists of iron as the remainder and inevitable impurities. Such composite steel achieves a tensile strength of up to 2000 MPa after hot forming and cooling.

[0030] As already mentioned, the annealing (working step b)) completed in four uninterrupted sequential steps A, B, C, D for each processed flat steel product generates a surface that is almost completely, i.e., at least 70%, especially at least 80%, or at least 90% covered by pure Fe. For this purpose, in zones A - D of the continuous annealing furnace used according to the invention, dew points and annealing temperatures specifically adapted to each case are set.

[0031] The annealing carried out in zones A - D in working step b) is performed in an annealing atmosphere containing 0.1 - 15 vol% hydrogen in each case, and the remainder in each case consists of nitrogen and inevitable impurities, and the total of the impurities is usually 5 vol% or less, especially 4 vol% or less, or preferably 3 vol% or less.

[0032] The annealing temperatures GT provided in the following and in the claims A 、GT B 、GT C 、and GT D All information about are indicating the average furnace chamber temperature during strip throughput.

[0033] Before entering Zone A of the continuous furnace operated according to the present invention, the surface of the flat steel product provided according to the present invention has a wide range of oxide products, which have an adverse effect on the quality of the coating, particularly on pore formation of the coating. By the conversion of these oxides by continuous annealing according to the present invention, only Fe in a technical sense is present on the surface of the flat steel product after annealing.

[0034] Dew point temperature TP in Zone A of the continuous furnace A Set the temperature to -10℃ to -25℃, and set the annealing temperature GT A By setting the temperature to 800-950°C, oxides present on the flat steel product are covered with iron oxide. To achieve this in a particularly targeted manner, the annealing temperature GT in Zone A of the continuous furnace is set. A The temperature may be 810-940°C, and the dew point temperature TP A The temperature can be -15 to -25°C.

[0035] In zones B and C, iron oxide is reduced, resulting in the presence of iron on the surface after zone C. In zone B, the dew point temperature TP of the annealing atmosphere that is dominant there. B The temperature is then reduced to -27°C to -41°C, and the annealing temperature GT B The temperature is maintained at 800-930°C, where the annealing temperature GT in Zone B of the continuous furnace is maintained in the case of annealing completed in step b). B It has been proven that the reliability of the desired effect is particularly high when the temperature is between 800 and 900°C.

[0036] In Zone C, the dew point temperature TP of the annealing atmosphere that is dominant there C The temperature is then further reduced to -30°C to -80°C, and the annealing temperature GT C The reduction from iron oxide to iron is completed by maintaining the temperature at 800-950°C. In the case of annealing completed in zone C of the continuous furnace in step b), the annealing temperature GT C The temperature is 800-920°C, and the dew point temperature TPC This effect can be achieved with particular reliability when the temperature is between -30°C and -50°C.

[0037] In Zone D, the dew point temperature TP of the annealing atmosphere that is dominant there D The temperature is then raised to -30°C to -20°C, and the annealing temperature GT D By maintaining the temperature at 750-950°C, the flat steel product can be recrystallized on the one hand, while the flat steel product is tempered in such a way that the previously achieved pure iron surface is preserved. In the case of annealing completed in zone D of the continuous furnace in work step b), the annealing temperature GT D This effect can be achieved with particular reliability when the temperature is between 780 and 930°C.

[0038] The lambda value λ describes the ratio of the mass of air to the mass of fuel introduced into the continuous furnace, and is typically 0.95 to 1.1 in the annealing atmosphere maintained in zones A to D of the continuous furnace used according to the present invention in the case of annealing completed in working step b) of the method according to the present invention.

[0039] A prerequisite for the effects achieved according to the present invention is the presence of at least one alkaline earth or transition metal in the aluminum (Al)-based corrosion protection coating applied after annealing (working step b)) according to the present invention. Thus, the coating of flat steel products treated according to the present invention after application of the corrosion protection coating (working step c)) and before heating for hot forming (working step f)) contains at least 0.1 to 5% by weight of at least one alkaline earth or transition metal, as well as the remainder Al and unavoidable impurities. Here, it has been proven that an alkaline earth or transition metal content of at least 0.11% by weight is particularly preferable in terms of reliability, thereby taking advantage of the positive effects of the presence of at least one alkaline earth or transition metal in the coating applied according to the present invention. If the alkaline earth or transition metal content exceeds 5% by weight, surface quality may be reduced due to increased oxide formation in the molten crucible. Excess oxides may also be formed during hot forming, which on the one hand promotes the splitting of water into hydrogen and oxygen, and as a result there is a risk that more hydrogen will enter the steel. On the other hand, a thicker oxide layer can lead to increased contamination in the molding tool. To reliably avoid this effect, the content of alkaline earth metals or transition metals in the corrosion-protective coating applied in step c) can be limited to 1.5% by weight or less in total, and particularly to 0.6% by weight or less. Therefore, the content of alkaline earth metals or transition metals in the corrosion-protective coating applied in step c) is particularly 0.11 to 1.5% by weight, or particularly 0.11 to 0.6% by weight.

[0040] As already mentioned, Mg, among the alkaline earth or transition metal groups, has proven particularly suitable for the purposes of the present invention, and in order to utilize the effects required by the present invention, Mg may be present alone in the coatings applied according to the present invention, or in combination with other alkaline earth or transition metals such as beryllium, calcium, strontium, and barium.

[0041] Optionally, silicon ("Si") in a content of up to 15% by weight, particularly up to 11% by weight, may also be present in the coating applied in work step c) to promote the formation of an iron-aluminum layer, which adheres well to the iron surface set in work step b) and accounts for no more than one-third of the total layer thickness of the coating. If the Si content is too high, it may result in a loss of adhesion due to an excessively large alloy layer thickness. A Si content of at least 3% by weight, particularly at least 8.5% by weight, has been proven to be particularly preferable in this regard, and thus, with a Si content of 3–15% by weight, particularly 3–11% by weight, particularly 8.5–11% by weight, the positive effect of Si can be used particularly reliably in practice.

[0042] In addition, the coating applied in step c) may optionally contain up to 5% by weight of Fe, particularly up to 4% by weight, and especially up to 3.5% by weight. The amount of iron in the coating may be set in this order of magnitude because this is the saturation value for aluminum molten material in the temperature range of 650–720°C. By specifically adding iron to the molten material, the risk of the iron component of the molten crucible in contact with the molten material dissolving can be reduced. In this regard, an Fe content of at least 1% by weight has been proven to be particularly preferable, and therefore, in practice, the positive effect of Fe can be reliably utilized with Fe content of 1–5% by weight, particularly 1–4% by weight, and especially 1–3.5% by weight.

[0043] The corrosion-protective coating can be applied in any known manner during step c) of the method according to the present invention. In this case, so-called "hot-dip aluminizing" is particularly preferred, in which each flat steel product is guided through a suitably heated molten bath configured according to the specifications of the present invention. Such hot-dip coating is particularly preferred for strip-shaped flat steel products having a maximum thickness of 3 mm. For greater thicknesses, one of the vapor deposition processes (PVD, CVD) mentioned earlier may also be used to apply the corrosion-protective coating.

[0044] In step c), the load of the corrosion-protective coating applied according to the present invention is typically 30-100 g / m² per side. 2 Especially 40-80g / m 2 Therefore, the total load on both sides of the coating is 60-200 g / m². 2 That is the case.

[0045] After the application of the corrosion-protective coating (work step c)), the coated flat steel product can optionally undergo cosmetic rolling (work step d) to set the mechanical characteristics of the flat steel product, adjust its surface roughness, or homogenize it. The resulting formability (formability = (thickness before cosmetic rolling - thickness after cosmetic rolling) / (thickness before cosmetic rolling)) is typically 0.1-5%.

[0046] After the application of a corrosion-protective coating (work step c)) or optional cosmetic rolling (work step d)), the board is separated from the flat steel product by a known method if necessary, and the dimensions of the board are adapted by a known method to the dimensions of the sheet metal component from which it is to be hot-formed (work step e)).

[0047] The flat steel product itself or the board is then heated to a hot forming temperature in work step f), which is higher than the Ac3 temperature of the steel of the flat steel product and not exceeding 1000°C, in particular equal to at least Ac3 temperature + 50°C and 980°C or less, where a hot forming temperature of 820-950°C has been proven to be particularly favorable. The flat steel product is held at this temperature until a sufficient amount of heat is introduced into the flat steel product or the board separated therefrom. The required holding time and annealing temperature in each case can be estimated based on the condition that the amount of thermal energy J introduced into the flat steel product or board in work step f) should be higher than 100,000 kJ and 800,000 kJ or less, where J can be calculated according to the following known equation. J[kJ]=[(T2-T1)xcxtxm] / 1000; Here, T2: The final temperature of the component at the end of heating at K T1: Starting temperature of the component at the start of heating at K c: Heat capacity of steel (typically 460 J / kgK) Holding time of flat steel products or boards at the final temperature at t:s Mass of flat steel products or boards in m:kg

[0048] Heating can be carried out in any preferred manner. When a conventional continuous furnace is used for this purpose, the flat steel product or board is heated by radiant heat, and a suitable holding time is usually 100 to 900 s, preferably 180 to 720 s, and particularly 240 to 600 s. When a hot forming temperature of 850 to 930°C is selected, a holding time of 180 to 600 s, particularly 240 to 600 s, is generally sufficient in practice. As an alternative to the use of a continuous furnace, heating can also be carried out in, for example, a conventional chamber furnace.

[0049] The heating of the flat steel product or board can also be carried out in two steps, using a method known to the public, first achieving pre-alloying of the corrosion-protective coating, and then bringing the flat steel product or board to its respective hot-forming temperature.

[0050] A board or flat steel product heated to the hot forming temperature is typically inserted into a hot forming tool within a transition time of less than 15 seconds, and especially less than 10 seconds, where it is hot-formed into a component (work step g).

[0051] Subsequently, or simultaneously, the desired structure is generated in the relevant part of the component by cooling at least one part of the obtained component in a controlled manner known to itself. The cooling rate required for this is typically 20-500 K / s, with cooling rates higher than 30 K / s, especially higher than 50 K / s, being particularly practical. Cooling "at least one part" of the component of course also includes the possibility of cooling the entire component in the manner described above to generate a hardened structure throughout the entire component.

[0052] The present invention enables the production of sheet metal components manufactured from flat steel products, the steel substrate of which the flat steel product consists of steel (in weight %) comprising 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01% S, up to 1.0% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, where the total content of Cr and Mo is 1.0% or less, up to 0.2% Ca, especially up to 0.1% V, and the remainder being iron and unavoidable impurities, and is coated with a corrosion-protective coating. The corrosion protection coating consists of up to 15% Si (by weight), up to 5% Fe, a total of 0.1-5% of at least one alkaline earth or transition metal, and the remainder being Al and unavoidable impurities. The layer of corrosion protection coating adjacent to the steel substrate is an interdiffusion layer made of ferrite having a maximum Al content of 50% by weight, particularly at least 1% by weight of Al. In the cross-section of this interdiffusion layer, the percentage of surface covered by pores having a diameter of ≥0.1 μm is less than 10%, particularly less than 5%, and preferably less than 3%. The surface covered by pores in the interdiffusion layer is <300 μm over a measured length of 500 μm. 2 , especially 200 μm 2 Less than 100 μm, particularly preferably 100 μm 2 It is less than [value missing]. The thickness of the alloy layer here is 1 to 30 μm, preferably 2 to 20 μm, and particularly 4 to 16 μm.

[0053] The present invention will be described in more detail below using exemplary embodiments. [Brief explanation of the drawing]

[0054] [Figure 1] This figure shows a cross-section of a steel sheet of a sheet metal component manufactured according to the present invention by hot forming, at a magnification of 500x. This cross-section was prepared by etching with 3% nital in a conventional manner to clarify the layer structure present on the steel sheet. [Figure 2] Figure 1 is a schematic diagram showing a cross-section. [Modes for carrying out the invention]

[0055] Therefore, the corrosion-protective coating K formed on the steel substrate S includes an interdiffusion layer D directly connected to the steel substrate S, which substantially consists of alpha mixed crystals (i.e., ferrite) with an increased Al content, where Fe2Al5 is still present in the phase. The interdiffusion layer D is characterized by being homogeneous and uniform, and substantially non-porous.

[0056] In the direction of the free surface O of the corrosion protection coating K, a first Si-rich layer S1 is formed on the diffusion layer D. At the boundary between the diffusion layer D and the Si-rich layer S1, a small number of widely spaced pores P1 exist within the diffusion layer D.

[0057] A first intermediate layer Z1 is formed in the direction of the free surface O on the Si-rich layer S1, and this layer consists of aluminum-iron, with the majority being aluminum. Trace amounts of Si, alkaline earth metals and / or transition metals, as well as unavoidable impurities, may also be present in layer S1. The intermediate layer Z1 is non-porous.

[0058] A second Si-rich layer S2 exists in the direction of the free surface O on the intermediate layer Z1.

[0059] The second intermediate layer Z2 is formed in the direction of the free surface O on the Si-rich layer S2. Layer Z2 is also made of aluminum-iron, mostly aluminum, but alkaline earth metals and / or transition metals may also be present. Trace amounts of Si and unavoidable impurities may also be present. Intermediate layer Z2 is also non-porous.

[0060] The side of the second intermediate layer Z2 facing the free surface O is coated with an oxide layer OX, which substantially consists of aluminum, silicon, and alkaline earth and / or transition metal oxides. On the hot-formed component, an oxide layer with an average thickness of up to 1.5 μm may be present. On the surface of the oxide layer OX forming the free surface O of the corrosion-protective coating K, a small number of crater-shaped pores P2 open to the environment are formed, widely spaced from one another.

[0061] For comparison, components were formed from flat steel products coated with an AlSi coating according to a prior art sample described in European Patent No. 2086755(B1). The coating consisted of 9.5% Si, 3.5% Fe, and the remainder being aluminum and unavoidable impurities (by weight), and therefore did not contain alkaline earth metals or transition metals of the type added according to the present invention.

[0062] The steel substrate of the flat steel product consisted of (by weight %) 0.224% C, 0.25% Si, 1.16% Mn, 0.014% P, 0.002% S, 0.039% Al, 0.0034% N, 0.2% Cr, 0.03% Ti, and 0.0026% B.

[0063] Before forming the flat steel products with the metal coating, the flat steel products treated for comparison underwent annealing in a continuous furnace with four zones, where the dew point temperature TP and annealing temperature GT shown in Table 6 were set. The air ratio λ in the continuous furnace was 0.98.

[0064] For comparison, a five-layer corrosion protection coating was also fabricated on a conventionally manufactured component. However, compared to the number of pores in the coating of a conventionally manufactured component for comparison, the number of pores P2 in the oxide layer OX of the component manufactured according to the present invention was reduced by at least 25%, and the number of pores P1 in the diffusion layer D was reduced by at least 40% compared to the pores present in the corresponding layer of the corrosion protection coating of a conventionally manufactured component for comparison. After a furnace stay time of 600 s, the area covered by pores P1 in a measured length of 500 μm of layer D was 300 μm. 2 That was the case.

[0065] Reducing the pore size of P2 leads to a reduction in paint craters and improves adhesion and weldability. The pores of P2 have openings of a few nanometers toward the atmosphere. As is typically done with automobiles, when components are further processed after hot forming, they undergo cathode dipping paint in addition to a number of washing steps. Contact with aqueous solutions is unavoidable here. During washing, surfactants added to the washing water improve wettability and significantly reduce the surface tension of water, allowing water to enter the pores P2 of the layer. In the cathode dipping paint process as well, water can enter the open pores P2. In this particular case, the washing water also results in the separation of paint particles that cannot enter the pores P2 due to the size of the openings. The water present in the pores P2 then reaches its boiling point when the paint layer is baked, resulting in a gas phase, which, in a kind of boiling delay, explosively leaks through the paint into the environment. As a result of this reaction, so-called paint craters are formed, which, in addition to their visual impact, significantly reduce the effectiveness of the paint in terms of corrosion protection. In particular, with aluminum-based coatings, corrosion and paint penetration can occur at these points. The formation of visually noticeable red rust, which is formed due to the high iron content of the coating, is a particular problem for further treatment.

[0066] In addition, on surfaces with many open pores P2, the adhesive has a higher viscosity and cannot penetrate the pores P2. As a result, the surface coating by the adhesive may be incomplete. Cavities may also form within the pore area, resulting in impaired adhesion.

[0067] The pores P2 present in layer OX also cause changes in the current path within the material during resistance spot welding, which negatively affects weldability.

[0068] When the pore count is high, the surface area where water can split during oxidation in the hot forming process is also expanded. It is known that this diffused hydrogen can penetrate into the material, which increases the risk of hydrogen-induced cracking.

[0069] By minimizing the frequency of pore formation P2 during the manufacturing of sheet metal components according to the present invention, the risks associated with pore formation in conventionally manufactured components can be effectively reduced.

[0070] Reducing the number of pores P1 in the diffusion layer D also leads to an increase in the force that the adhesive can transmit and an improvement in weldability.

[0071] The pores P2 represent cavities within the corrosion-protective coating K. If there are too many pores, there is a risk that the corrosion-protective coating K will break down in the boundary region between the diffusion layer D and the first Si-rich layer S1, resulting in the adhesive seam also failing in the initial stages. By reducing the number of pores P1 achieved according to the present invention, the area over which the adhesive force is transmitted increases by more than 60%, and therefore the risk of delamination failure is reduced.

[0072] To demonstrate the effectiveness of the present invention, six steel sheets, each having a thickness of 1.5 mm and cold-rolled in a conventional manner, were manufactured from six steels, ST1 to ST6, the compositions of which are shown in Table 1 (working step a of the method according to the present invention).

[0073] The steel sheets provided in this manner underwent continuous annealing G1, G2, or G3 in a continuous furnace with four continuous zones A, B, C, and D in each of the nine tests V1 to V9. Table 2 shows the dew point temperature TP set in zones A to D for annealing deformations G1 to G3. A ~TP D Annealing temperature GT A ~GT D This also shows the hydrogen content H2 and nitrogen content N2 of each annealing atmosphere, the remainder of which consisted of technically unavoidable impurities (working step b of the method according to the present invention).

[0074] Each of the samples annealed in this manner is conventionally coated with Al-based corrosion protection coatings Z1-Z5 having a load AG. The compositions of the corrosion protection coatings Z1-Z5 are shown in Table 3 (working step c of the method according to the present invention).

[0075] Each sample, coated with one of the corrosion protection coatings Z1 to Z5, was subjected to hot forming at a continuous furnace temperature T in each of the tests V1 to V9. WU Heat to a certain temperature and hold at that temperature for a certain time t WU (working step f of the method according to the present invention) was held during this time.

[0076] The steels ST1 to ST6 that make up the samples used in each of Tests V1 to V9, the annealing deformations G1 to G3 used in each of Tests V1 to V9, the compositions Z1 to Z5 of the corrosion protection coatings produced in each of Tests V1 to V9 and their respective loads AG, and the hot forming temperature T selected in each of Tests V1 to V9. WU and retention time t WU This is shown in Table 4.

[0077] The heated samples were removed from the continuous furnace after a transition time of 3 to 7 seconds in each case and placed in a conventional hot forming tool, where the samples were hot-formed into components. Subsequently, in each case, the samples were cooled to room temperature at 270 K / s (working steps g) and h)) of the method according to the present invention).

[0078] Three cross-sections of the components obtained in tests V1 to V9 were generated using a known method, and these cross-sections were etched with 3% nital to clarify the layer structure. As an example, as shown in Figure 1, these cross-sectional images were generated at 500x magnification. In each image, the pores P1 and P2 present in layers OX and D were counted over a 550 μm length. In each case, an arithmetic mean was formed from the results of the counts defined for the three cross-sections of the sample. This arithmetic mean of the number of pores P1 and P2 was compared with a comparison value defined in the same manner for a comparison sample.

[0079] Table 5 shows the relative reductions in pore counts P1 and P2 achieved by the present invention, resulting from this comparison. Table 5 also shows the percentage of paint craters in the total area of ​​each sample, the reduction in delamination area, and the weld area as defined according to the steel test sheet SEP1220-2. Weld areas greater than 1 kA are classified as "OK".

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] [Table 4]

[0084] Table 5

[0085] Table 6

Claims

1. 1. A method for manufacturing sheet metal components from flat steel products provided with a corrosion-protective coating, comprising the following work steps: a) providing a flat steel product manufactured from steel comprising (in % by weight): 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, max 0.06% P, max 0.01% S, max 1.0% Al, max 0.15% Ti, max 0.6% Nb, max 0.01% B, max 1.0% Cr, max 1.0% Mo, where the sum of the Cr and Mo contents is equal to or less than 1.0%, max 0.2% Ca, max 0.1% V and the balance Fe and unavoidable impurities; b) annealing the flat steel product in a continuous furnace having four zones A, B, C, D, through which the flat steel product passes successively and in which it is annealed under an annealing atmosphere consisting in each case of 0.1 to 15% by volume of hydrogen and the balance nitrogen and technically unavoidable impurities, in which the annealing temperature GT A , G.T. B , G.T. C , G.T. D Dew point temperature TP A , T.P. B , T.P. C , T.P. D the annealing step, 【Table 0】 c) applying a corrosion-protective coating to the flat steel product obtained in process step b), said corrosion-protective coating consisting of (in % by weight): 3-15% Si, 1-5% Fe, a total of 0.1-5% of at least one alkaline earth metal, and the balance Al and unavoidable impurities; d) optionally decorative rolling said flat steel product provided with said corrosion protective coating; e) optionally separating boards from said flat steel products; f) heating the flat steel product or the board, if step e) has been performed, to a hot forming temperature above the Ac3 temperature of the steel of the flat steel product and not exceeding 1000°C, for a holding time sufficient to introduce into the flat steel product or into the board an amount of thermal energy Js of more than 100,000 kJs and not more than 800,000 kJs, Js is expressed by the following known equation: Js[kJs]=[(T2-T1)x c x t x m] / 1000; Where T2 is the final temperature of the component at the end of heating in K T1: starting temperature of the component at the beginning of heating in K c: Heat capacity of steel (usually 460 J / kgK) t: holding time of the flat steel product or board at the final temperature in s m: mass of the flat steel product or board in kg the heating step being calculated according to g) hot forming the flat steel product heated to the hot forming temperature or, if step e) has been performed, the board heated to the hot forming temperature into the sheet metal component; h) cooling at least one portion of said component at a cooling rate sufficient to produce a hardened structure in said portion of said sheet metal component; A method comprising:

2. 2. The method according to claim 1, characterized in that the thickness of the flat steel product provided in work step a) is between 0.6 and 7 mm.

3. In the case of the annealing completed in work step b), the annealing temperature GT in the zone A of the continuous furnace A is 810 to 940° C., and the dew point temperature TP A The method according to claim 1 or 2, characterized in that the temperature is between -15°C and -25°C.

4. In the case of the annealing completed in work step b), the annealing temperature GT in the zone B of the continuous furnace B The method according to any one of claims 1 to 3, characterized in that the heating temperature is between 800 and 900 °C.

5. In the case of the annealing completed in work step b), the annealing temperature GT in the zone C of the continuous furnace C is 800 to 920° C., and the dew point temperature TP C The method according to any one of claims 1 to 4, characterized in that the temperature is between -30°C and -50°C.

6. In the case of the annealing completed in work step b), the annealing temperature GT in the zone D of the continuous furnace D The method according to any one of claims 1 to 5, characterized in that the heating temperature is between 780 and 930 °C.

7. A method according to any one of claims 1 to 6, characterized in that the lambda value λ, representing the ratio of air mass to fuel in the annealing atmosphere introduced into the continuous furnace and maintained in zones A to D, is between 0.95 and 1.1 in the case of the annealing completed in work step b).

8. 8. The method according to claim 1, wherein the corrosion protective coating applied to the flat steel product in work step c) has a total content of alkaline earth metals of up to 0.6% by weight.

9. 9. Method according to any one of the preceding claims, characterized in that the corrosion protective coating applied to the flat steel product in work step c) contains magnesium as the at least one alkaline earth metal.

10. The coating weight of the corrosion protection coating applied to the flat steel product in work step c) is between 30 and 100 g / m2 per coated side of the flat steel product. 2 The method according to any one of claims 1 to 9, characterized in that

11. Method according to any one of the preceding claims, characterised in that in work step c) the corrosion protection coating is applied to the flat steel product by means of hot dip coating.

12. 12. Method according to any one of the preceding claims, characterized in that the heating of the flat steel products or boards in work step f) is carried out by radiant heat in a continuous furnace and the holding time is between 100 and 900 s.

13. 1. A sheet metal component manufactured from a flat steel product, the steel substrate of the flat steel product consisting of steel consisting of (in weight %) 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, max 0.06% P, max 0.01% S, max 1.0% Al, max 0.15% Ti, max 0.6% Nb, max 0.01% B, max 1.0% Cr, max 1.0% Mo, where the sum of the Cr and Mo contents is less than or equal to 1.0%, max 0.2% Ca, max 0.1% V and the balance Fe and unavoidable impurities, and coated with a corrosion protective coating. % of at least one alkaline earth metal, the balance being Al and unavoidable impurities, and the layer of the corrosion protective coating adjacent to the steel substrate is an interdiffusion layer (D) consisting of ferrite with an Al content of up to 50% by weight, in a cross section of the interdiffusion layer (D) the proportion of the surface covered by pores having a diameter of ≥ 0.1 μm is less than 10%, and the surface covered by pores in the interdiffusion layer (D) is < 300 μm over a measured length of 500 μm. 2 , sheet metal components.

14. A sheet metal component according to claim 13, characterized in that the interdiffusion layer (D) has a thickness of 1 to 30 μm.